SARS-CoV-2 Persistent Viral Shedding in the Context of Hydroxychloroquine-Azithromycin Treatment - Michel Drancourt; Sébastien Cortaredona; Cléa Melenotte; Sophie Amrane; Carole Eldin; Bernard La Scola; Philippe Parola; Matthieu Million; Jean-Christophe Lagier; Didier Raoult; Philippe Colson (Viruses, 2021)
SARS-CoV-2 nasopharyngeal shedding contributes to the spread of the COVID-19 epidemic. Among 3271 COVID-19 patients treated at the Hospital University Institute Méditerranée Infection, Marseille, France from 3 March to 27 April 2020, tested at least twice by qRT-PCR, the median SARS-CoV-2 nasopharyngeal shedding duration was 6 days (range 2–54 days). Compared with short shedders (qRT-PCR positivity < 10 days), 34 (1.04%) persistent shedders (qRT-PCR positivity ≥ 17 days; mean ± SD: 23.3 ± 3.8 days) were significantly older, with associated comorbidities, exhibiting lymphopenia, eosinopenia, increased D-dimer and increased troponin (p < 0.05), and were hospitalized in intensive care unit in 17.7% vs. 1.1% of cases (p < 0.0001). Viral culture was positive in six persistent shedders after day 10, including in one patient after day 17, and no viral co-pathogen was detected in 33 tested patients. Persistent shedders received azithromycin plus hydroxychloroquine ≥ 3 days in 26/34 (76.5%) patients, a figure significantly lower than in short shedders (86.6%) (p = 0.042). Accordingly, mortality was 14.7% vs. 0.5% (p < 0.0001). Persistent shedding was significantly associated with persistent dyspnea and anosmia/ageusia (p < 0.05). In the context of COVID-19 treatment, including treatment with azithromycin plus hydroxychloroquine, the persistence of SARS-CoV-2 nasopharyngeal shedding was a rare event, most frequently encountered in elderly patients with comorbidities and lacking azithromycin plus hydroxychloroquine treatment.